(untitled) (CIPEEX, 2025)
This study analyzes the security of Brazilian electronic voting machines, a system that, since 1996, has fully computerized the electoral process in the country. This technological innovation represented a landmark in the nation’s democratic history, providing greater speed in vote counting and eliminating manual stages susceptible to errors and manipulation. As a result, it became possible to announce election results almost immediately after the polls closed, strengthening the principle of promptness and significantly contributing to the credibility of the electoral system. Computerization also expanded popular participation, as it facilitated the exercise of voting, especially in remote areas or locations with limited infrastructure. In addition, electronic voting machines have enabled access to a more inclusive and secure electoral process, reflecting the technological advances incorporated by Brazil’s public administration. The objective of this study is to evaluate the effectiveness of existing protection mechanisms, identify potential vulnerabilities, and propose improvements to strengthen the security and transparency of the electoral process. The methodology was based on the analysis of legal and technical articles and research, considering electoral principles, the audits carried out, and the information security standards adopted by the Superior Electoral Court (TSE). The results show that voting machines include various protection measures, such as physical seals, public audits, civil society participation, and technical tests conducted by specialists. It is concluded that, although there are criticisms and aspects that can be improved, electronic voting machines are, in essence, secure. However, it is essential to continuously invest in oversight and auditing mechanisms.